RANCANG BANGUN BANTALAN MAGNET PERMANEN UNTUK RODA DAYA SEBAGAI BATERAI MEKANIK - Renova Sibarani; Stenly Tangkuman; Michael Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2021)
The flywheel as a mechanical battery is an energy storage device that is superior in terms of charging and discharging compared to other energy storage devices. In this research the dimensions of the mechanical battery are design in a such a way as to make it easier to use in daily life. On other side the mechanical battery is designed using permanent magnet bearing in the hope that it can minimize the occurance of frictionthat can reduce the power of the battery.The research was made in a Design and ConstructionLaboratory, Majoring in Mechanical Engineering UNSRAT. In this research the shaft material used is carboon steel type S30C which is heat treat with normalization. The shaft diameter is obtained 18 mm and flywheel diameter is 100 mm. Magnet capacity on the shaft as many as 28 magnets on each ring. So the total magnet on the shaft are 224 magnets. Aside on that in this research the diameter of the bearing is 30 mm with magnet capacity is 40 magnets on each ring. So the total magnet on the bearing are 320 magnets.The final result of the mechanical battery dimensions is 110Ã—120Ã—105 mm. the magnitude of the magnetic support force on each ring is 900 gr with the total bearing support force is 7,2 kg. The maximum torque that can be held is 4574 kg.mmÂ Keyword : Mechanical Battery, Dimensions, Magnetic Bearing